Identifikasi Jenis-Jenis Avertebrata Air Di Pasar Ikan Pangkalpinang - Stevani Mannadona Hutajulu; Intan Viora Retasya; Arini Ulfa Mawaddah; Ahmad Sutra; Rifki Septio; Sakti Immanuel Jasa Silalahi; Ardiansyah Kurniawan (CV. SINAR HOWUHOWU, 2025)
The Bangka Belitung Islands, recognized as one of Indonesia’s key capture fisheries production centers, also possess substantial potential for the production of economically valuable aquatic invertebrates. Pangkalpinang City, serving as the commercial hub of the province, hosts a major trading center for aquatic invertebrates alongside other fishery commodities at the Pangkalpinang Fish Market. This study identified the types of aquatic invertebrates traded at the Pangkalpinang Fish Market. The species of aquatic invertebrates recorded during the survey conducted in November 2025 were squid (Loligo sp.), whiteleg shrimp (Litopenaeus vannamei), mud crab (Scylla serrata), blood cockle (Anadara granosa), and local clam (Polymesoda erosa). Aquatic invertebrate species that were not found during the survey included the gonggong snail (Strombus canarium), cuttlefish (Sepia officinalis / Sepia pharaonis), blue swimming crab (Portunus pelagicus), and mantis shrimp (Harpiosquilla raphidea).